Possible immunochemical pattern of anti-HCV, HBeAg, HBsAg HBeAb, and HIV-1 p24 in newly infected Mycobacterium pulmonary tuberculosis patients - Mathew Folaranmi Olaniyan; Ruth Aderibigbe; Temitayo Afolabi (Wolters Kluwer Medknow Publications, 2019)
Background: Viral biomarkers in pulmonary tuberculosis (PTB) could be a primary or secondary viral infection to PTB which may depressed immunity or make the patient susceptible to the secondary infection. Aim and Objective: This work was, therefore, designed to determine frequency of anti-hepatitis C virus (HCV), hepatitis B envelope antigen (HBeAg), hepatitis B surface antigen (HBsAg), hepatitis B envelope antibody (HBeAb), and human immunodeficiency virus (HIV)-1 p24 in newly infected Mycobacterium PTB patients. Materials and Methods: Sixty newly infected Mycobacterium tuberculosis patients were recruited from the medical outpatient Department of Baptist Medical center, Saki-Nigeria. The patients were classified into females (30) and males (30) aged 38-79 years. M. tuberculosis was determined in the patients through fluorescence immunoassay, cultivation of sputum sample on Löwentein-Jensen medium, and radiological chest X-ray report. Anti-HCV, HBeAg, HBsAg HBeAb, and HIV-1 p24 were determined in the patients by immunochromatography and ELISA methods. Results: The viral immunochemical pattern obtained in the newly infected PTB patients showed a frequency of: 5% (3) (males - 3.3% [2] and females - 1.67% [1]) anti-HCV; 3.3% (2) (all males - 3.3% [2]) HIV-1 - p24; 15% (9) (males - 3 [5%] and females - 6 [10%]) HBsAg; 9 (15%) (males - 5% [3] and females - 10% [6]) HBeAg; 18.33% (11) (males - 6.7% [4] and females - 11.67% [7]) hepatitis B envelope (HBe) antibody; 3.33% (2) (males - 1.67%[1] and females - 1.67% [1]) HBeAg + HBsAg + HIV-1 - p24. Conclusion: This work revealed evidence of anti-HCV; HIV-1 - p24; HBsAg; HBeAg; and HBe antibody and HBeAg + HBsAg + HIV-1 - p24 in newly infected pulmonary M. tuberculosis-infected patients. Routine evaluation of viral biomarkers in PTB patients is necessary for effective management.